Workshop Publik Speaking Santriwati Pondok Pesantren Rooihatul Jannah Dalam Meningkatkan Skill Presentasi - Dani Kurniawan; Muhammad Zulfi Ifani; Linda Trilestari; Azzahrah Miftahul Jannah (Universitas Muhammadiyah Klaten, 2024)
This study aims to improve the public speaking skills of female santri of Pondok Pesantren Rooihatul Jannah Sukoharjo through specially designed workshops. This research is motivated by the importance of public speaking skills in various aspects of life, especially in the context of da'wah. The method used in this research is experimental method with qualitative approach. Data collection was done through pre-test, workshop implementation, and post-test. The results showed that the public speaking workshop significantly increased self-confidence, overcame stage fright, and overcame blank material in participants. In addition, participants also gave positive responses to the materials and methods presented. The conclusion of this study is that public speaking workshops can be an effective solution in improving the communication skills of santriwati and make a positive contribution to their self-development.